Managers' Perceptions of the Impact of Cultural Differences on the Process of Internationalization of Polish Companies - Aleksandra Olejnik Nizielska; Jorma Larimo (Theory, Methodology, Practice, 2015)
A large sector of researchers in the International Business field, along with those in other fields (such as International Marketing and International Management), have dedicated themselves to research involving the reliability, applicability and generalizability of the psychic distance phenomenon.This construct has an influence on theinternationalization of companies. The aim of the article is to present qualitative research results on managers’ perceptions of the importance of one of the psychic distance stimuli, namely cultural differences,in the process of internationalization of companies. In the theoretical section of the article, the definition and operationalization of psychic distance and different stimuli of this construct are described.Particular consideration is dedicated tocultural differences. The second part of the article focuseson the research background.In the third part of the article, the importance of the differences in culture in the process ofinternationalization isevaluated. The article presents the respondents’ opinions on the significance of cultural values and practices, differences in religion and differences in languages in managers’ decisions on internationalization. The authorsfocus on the impact of cultural differences on the choice of directions of foreign expansion, market entry strategies, the amount of foreign expansion markets, the pace of internationalization as well as the value of sales and capital engagement abroad.